Septic thrombophlebitis with persistent methicillin-resistant Staphylococcus aureus bacteremia and de novo resistance to vancomycin and daptomycin - Yael Koton; Zafrir Or; Naiel Bisharat (MDPI AG, 2017)
Persistent methicillin-resistant Staphylococcus aureus (MRSA) bacteremia is associated with significant risk of mortality, especially when it occurs while on appropriate antimicrobial therapy. We herein describe an unusual case of a patient with prosthetic aortic tissue valve, who suffered from central venous catheter related MRSA bacteremia with septic thrombus formation in the superior vena cava. MRSA bacteremia persisted despite removal of the catheter and appropriate antimicrobial therapy including vancomycin, rifampin, and daptomycin. Subsequently, the MRSA strain exhibited de novo resistance to vancomycin, rifampin and daptomycin. Eventually, salvage combination therapy with high dose daptomycin and trimethoprim-sulfamethoxazole was successful and achieved clearance of MRSA bacteremia. The case illustrates the growing complexity of treating MRSA infections.